WEBVTT
00:00:01.000 --> 00:00:12.350
Simplify 𝑏 to the power of four multiplied by 𝑎 to the power of four multiplied by 𝑏 to the power of two multiplied by 𝑎 to the power of five.
00:00:13.320 --> 00:00:25.640
Our first step is to group the like terms: 𝑎 to the power of four multiplied by 𝑎 to the power of five and the 𝑏 terms, 𝑏 to the power of four multiplied by 𝑏 to the power of two.
00:00:27.010 --> 00:00:29.340
We can then use one of the laws of exponents.
00:00:29.750 --> 00:00:37.100
𝑥 to the power of 𝑎 multiplied by 𝑥 to the power of 𝑏 is equal to 𝑥 to the power of 𝑎 plus 𝑏.
00:00:38.430 --> 00:00:51.100
Using this law on the 𝑎 terms, 𝑎 to the power of four multiplied by 𝑎 to the power of five means that we can add the two exponents or powers, giving us 𝑎 to the power of four plus five.
00:00:52.410 --> 00:00:58.650
In the same way, we can add the exponents or powers of the 𝑏 terms, 𝑏 to the power of four plus two.
00:01:00.200 --> 00:01:04.160
Four plus five is equal to nine, and four plus two is equal to six.
00:01:04.560 --> 00:01:11.490
Therefore, simplifying this expression gives us 𝑎 to the power of nine multiplied by 𝑏 to the power of six.
00:01:12.700 --> 00:01:20.260
As multiplication is commutative, this could also be written as 𝑏 to the power of six multiplied by 𝑎 to the power of nine.